2022
DOI: 10.1021/acs.langmuir.2c02093
|View full text |Cite
|
Sign up to set email alerts
|

Unveiling the Mechanism of Frictional Catalysis in Water by Bi12TiO20: A Charge Transfer and Contaminant Decomposition Path Study

Abstract: Tribocatalysis, as a new approach in environmental purification, has drawn increasing attention in the past few years. In this work, we successfully convert mechanical energy to chemical energy by Bi12TiO20, which was synthesized by a hydrothermal method. Under magnetic stirring, electrons transfer from the surface of Bi12TiO20 to the polytetrafluoroethylene-sealed magnetic bar due to their friction. Moreover, the holes that remain on Bi12TiO20 provide oxidation properties in the process for organic matter deg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(6 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…Tribocatalysis, as a method for converting mechanical energy into chemical energy, has been proven to be an effective means of utilizing mechanical energy. [19][20][21] In recent years, friction energy has been increasingly utilized in the field of catalysis, leading to numerous reports on the degradation of dyes by tribocatalysis, using Ba 0.75 Sr 0.25 TiO 3 , 22 Bi 2 WO 6 , 23 Bi 12 TiO 20 , 24 and FeS 2 . 25 In comparison with other materials, polytetrafluoroethylene (PTFE) exhibits facile electron access during friction, outstanding temperature adaptability, chemical inertness, resilience to strong acids and bases, and exceptional aging resistance.…”
Section: Introductionmentioning
confidence: 99%
“…Tribocatalysis, as a method for converting mechanical energy into chemical energy, has been proven to be an effective means of utilizing mechanical energy. [19][20][21] In recent years, friction energy has been increasingly utilized in the field of catalysis, leading to numerous reports on the degradation of dyes by tribocatalysis, using Ba 0.75 Sr 0.25 TiO 3 , 22 Bi 2 WO 6 , 23 Bi 12 TiO 20 , 24 and FeS 2 . 25 In comparison with other materials, polytetrafluoroethylene (PTFE) exhibits facile electron access during friction, outstanding temperature adaptability, chemical inertness, resilience to strong acids and bases, and exceptional aging resistance.…”
Section: Introductionmentioning
confidence: 99%
“…15 The transferred electrons that directly participated in chemical reactions achieve tribocatalysis. 16 Materials that gain or lose electrons contribute to the generation of active species to participate in the next redox reaction. 17 In electron transition, mechanical energy excites electrons in the valence band (VB) to the conduction band (CB), leaving holes in the valence band and electrons on the conduction band.…”
Section: Introductionmentioning
confidence: 99%
“…In 2019, Li et al have already reported that Ba 0.75 Sr 0.25 TiO 3 nanoparticles can be used for dye degradation by harvesting mechanical energy from the environment. Subsequently, a series of catalysts, such as BiOIO 3 , ZnO, CdS, Bi 12 TiO 20 , Bi 2 WO 6 , TiO 2 , NiCo 2 O 4 , Ba 4 Nd 2 Fe 2 Nb 8 O 30 , Ba 2.5 Sr 2.5 Nb 8 Ta 2 O 30 , and so on, have been used for tribocatalysis. However, most of the currently reported tribocatalysts confront improving the catalytic efficiency, reducing the cost, and preventing secondary pollutant generation from the use of non-environmental protection powder catalysts.…”
Section: Introductionmentioning
confidence: 99%